Effects of Intense Endurance Exercise on Serum Levels of Zinc and Copper in Elite Rowers - Hazar, Muhsin (Asian Journal of Chemistry, 2010)
The aim of this study was to investigate serum levels of zinc and copper in well-trained individuals of men's rowing team during and after aerobic maximal intensity endurance exercise. Eleven well-trained young male completed the exercise protocol. Blood samples were collected before, immediately after exercise and 1 h after exercise. Serum was analyzed for Zn and Cu by using inductively coupled plasma optical emission spectrometry (ICP-OES) method. Both of Zn and Cu levels decreased significantly (p < 0.05) in serum samples collected 1 h after exercise while no significant change (p > 0.05) for Zn and Cu was observed in serum samples collected immediately after exercise in comparison to the resting levels.